2015
DOI: 10.1155/2015/653740
|View full text |Cite
|
Sign up to set email alerts
|

TheCortinariusFungi Dyes as Sensitizers in Dye-Sensitized Solar Cells

Abstract: The dye-sensitized solar cells have been for the first time prepared usingCortinariusfungi extracts as a source of sensitizing dyes. The seven species ofCortinariusgroup, collected in the East Poland, have been used to obtain crude extracts of natural dyes used as sensitizing solutions to prepare DSSCs working electrodes. Extracts and sensitized electrodes have been well characterized by UV-Vis spectroscopy measurements. The device sensitized byCortinarius sanguineusextract has been found the most active in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Quinone dyes have been used for various applications, such as histological staining, rust prevention on metal surfaces, and increasing the conversion efficiency of solar cells, and they have found use as sensors, pH indicators, pigments, inks and dyes for leather, wood, medicine, food and textiles [5,64,65,190,191]. Of these uses, the most popular one is colouration of textiles, whereas their application in bio-inspired systems for energy harvesting and storage is a more recent development.…”
Section: Applications Of Natural Quinone Dyementioning
confidence: 99%
“…Quinone dyes have been used for various applications, such as histological staining, rust prevention on metal surfaces, and increasing the conversion efficiency of solar cells, and they have found use as sensors, pH indicators, pigments, inks and dyes for leather, wood, medicine, food and textiles [5,64,65,190,191]. Of these uses, the most popular one is colouration of textiles, whereas their application in bio-inspired systems for energy harvesting and storage is a more recent development.…”
Section: Applications Of Natural Quinone Dyementioning
confidence: 99%
“…In the case of the longer exposure time of the oxide with the undiluted dye, a higher absorbance is obtained with an approximate value of 3, this highest point is at 600 nm and belongs to the exposure time of the dye of 4 h, compared to the spectra obtained from the dye. The groups present in the carotenoid molecule bind with the copper oxide film and this generates an alteration that is attributed to the decrease and the fact that the absorbance is shifted to the right, this not only happens with copper compounds, it also happens with TiO 2 that as presented in his work Maciej Zalas [17], also when in contact with the compounds of the carotenoid molecule do not present the same absorption as the dye alone. that there are no changes in terms of the characteristic peaks of the mentioned materials, it is only observed that there is a small edge at the beginning of the x-axis, this is due to the presence of a coloring compound, it is observed that the copper deposit does not contain impurities since the peaks of copper and ITO are very well defined [19].…”
Section: Sensitization Of the Copper Oxide Electrodepositmentioning
confidence: 97%
“…To date, only two species of medicinal mushroom dyes have been tested in DSSCs, the Button mushroom Agaricus bisporus [116] and pale-brown Cortinarius sp. [117], both of which are successful in the field. These two species contain significant amounts of electron-absorbing dyes extracted from the fruiting body and act as sensitizers in the DSSC system.…”
Section: Medicinal Mushroom Dye As An Active Photo-energy Conversion ...mentioning
confidence: 99%